Material constraints related to storage of future European renewable electricity surpluses with CO2 methanation. (July 2016) - Meylan, Frédéric D.; Moreau, Vincent; Erkman, Suren
Abstract: The main challenges associated with a growing production of renewable electricity are intermittency and dispersion. Intermittency generates spikes in production, which need to be curtailed when exceeding consumption. Dispersion means electricity has to be transported over long distances between production and consumption sites. In the Directive 2009/28/EC, the European Commission recommends sustainable and effective measures to prevent curtailments and facilitate transportation of renewable electricity. This article explores the material constraints of storing and transporting surplus renewable electricity by conversion into synthetic methane. Europe is considered for its mix of energy technologies, data availability and multiple energy pathways to 2050. Results show that the requirements for key materials and land remain relatively low, respecting the recommendations of the EU Commission. By 2050, more than 6 million tons of carbon dioxide might be transformed into methane annually within the EU. The efficiency of renewable power methane production is also compared to the natural process of converting solar into chemical energy (i.e. photosynthesis), both capturing and reenergizing carbon dioxide. Overall, the production of renewable methane (including carbon dioxide capture) is more efficient and less material intensive than the production of biofuels derived from photosynthesis and biomass conversion. Highlights: The potential of methanation to store renewable electricity surpluses is assessed. Material constraints are relatively low. Biogenic CO2 will probably be insufficient. Production of renewable power methane is more efficient than conventional biofuels. Renewable power methane can help decarbonizing the global energy sector.